2019
DOI: 10.1093/ecco-jcc/jjz041
|View full text |Cite
|
Sign up to set email alerts
|

Higher Trough Vedolizumab Concentrations During Maintenance Therapy are Associated With Corticosteroid-Free Remission in Inflammatory Bowel Disease

Abstract: Background and Aims Vedolizumab is an anti-α4β7 biologic approved for ulcerative colitis [UC] and Crohn’s disease [CD]. We aimed to examine the association of maintenance vedolizumab concentrations with remission. Methods We performed a cross-sectional multi-centre study of inflammatory bowel disease [IBD] patients on maintenance vedolizumab. A homogeneous mobility shift assay [HMSA] was used to determine trough serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 22 publications
0
36
2
Order By: Relevance
“…From 12 104 studies identified using the original search strategy, 5655 unique studies were identified. From these, 32 studies focusing on vedolizumab were identified for full text review, and five studies were included in quantitative synthesis (Figure ) . Additionally, data from five studies was qualitatively synthesized to inform vedolizumab concentrations associated with favourable outcomes .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From 12 104 studies identified using the original search strategy, 5655 unique studies were identified. From these, 32 studies focusing on vedolizumab were identified for full text review, and five studies were included in quantitative synthesis (Figure ) . Additionally, data from five studies was qualitatively synthesized to inform vedolizumab concentrations associated with favourable outcomes .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the GEMINI‐2 trial in patients with Crohn's disease, steady state vedolizumab trough concentration in quartiles 2‐4 (≥7.6 μg/mL) was associated with numerically higher rates of clinical remission (83%‐89% vs quartile 1, 67%) . In an observational study, Ungaro and colleagues reported that vedolizumab trough concentration ≥11.3 μg/mL during maintenance therapy had the most optimal, yet modest, discriminatory performance for assessing the presence of corticosteroid‐free clinical and biochemical remission in patients with IBD (AUROC, 0.62; sensitivity/specificity, 0.57/0.63); specifically, in patients with ulcerative colitis, the cut‐off was ≥10.1 μg/mL (sensitivity/specificity, 0.89/0.43) and in patients with Crohn's disease, the cut‐off was ≥6.8 μg/mL (sensitivity/specificity 0.83/0.38) . A cut‐off of ≥10.7 μg/mL was most discriminative for the presence of corticosteroid‐free endoscopic remission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations